Impact of immunochemotherapy regimens on outcomes of patients with primary mediastinal B-cell lymphoma in the IELSG37 trial - Zucca, Emanuele; Ceriani, Luca; Ciccone, Giovannino; Di Rocco, Alice; Pirosa, Maria Cristina; Kriachok, Iryna; Botto, Barbara; Balzarotti, Monica; Tucci, Alessandra; Usai, Sara Veronica; Zilioli, Vittorio Ruggero; Pennese, Elsa; et al. (Blood, 2025)
The IELSG37 trial enrolled 545 patients with primary mediastinal B-cell lymphoma (PMBCL) and demonstrated that consolidation radiotherapy (RT) can be omitted in patients with complete metabolic response, defined by the Lugano classification as Deauville score (DS) 1 to 3. This report evaluates outcomes after different frontline rituximab- and doxorubicin-based immunochemotherapy regimens chosen according to local practice. Patients treated with R-CHOP21 (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone, administered every 21 days) showed a significantly higher percentage of DS 5 than those on other regimens (23.8% vs 8.2% average; P < .001) and a trend toward additional unplanned treatments (53.2% vs 46.9%; P = .30). The increased risk of poor response was confirmed in a multinomial logistic regression analysis adjusted for age, sex, international prognostic index score, and performance status. R-CHOP21 was also associated with smaller reductions in metabolic tumor volume and less pronounced decreases in maximum standardized uptake value. Patients with DS 5 more often received additional treatment (RT and/or salvage chemotherapy with or without autologous consolidation) after induction immunochemotherapy (96% vs 41%; P < .001) and experienced significantly poorer outcomes. Although differences in progression-free and overall survival between R-CHOP21 and more aggressive regimens were not statistically significant, R-CHOP21 may increase the risk of additional treatments and may be inadvisable as frontline therapy for PMBCL. This trial was registered atwww.clinicaltrials.govas #NCT01599559.
Publisher Copyright: © 2025 American Society of Hematology. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.